The Effective Diagnosis of Chronic Monoarthropathy: What are Our Options? - Anil, V.; Nekkanti, Supreeth; Kukralia, Abhimanyu; Mahajan, Ramneek; Mahtani, Arun (Nigerian Journal of Orthopaedics and Trauma, 2018)
Introduction: Monoarticular arthritis which means inflammation, (infective or non-infective) of single synovial joint is a huge burden in the health care system. Chronic monoarthritis is characterized by its progressive onset and slow development, commonly presenting with mild inflammatory signs. The clinical presentation is usually nonspecific especially in the early stages. To evaluate the role of clinical, hematological and immunological features in the diagnosis of peripheral large joint monoarthritis and its correlation with radiographic studies and histopathological studies of the same. Materials: A total of 30 patients of a monoarticular joint disease were studied in which conventional radiography, MR imaging, arthroscopy and synovial biopsy as techniques for its diagnosis were compared. Results: The mean age in the present study was 21.23 years with a preponderance of male patients. MRI was found to have high sensitivity (87.5%) and specificity (85.7%) in the diagnosis of chronic inflammatory synovitis. Arthroscopy wasfound to have a sensitivity of 83-85% and specificity of 85-86% in diagnosing both inflammatory and infective synovitis. Conclusion: MRI is recommended as additional techniques in the initial diagnostic evaluation when radiography yields negative results. When assessed together with ahistopathological examination of the synovium and mycobacterial cultures, MRI imaging forms a powerful tool in diagnosing tubercular synovitis early. Arthroscopic joint evaluation should be used wherever feasible for a complete evaluation of the knee joint along arthroscopic guided biopsy. Not only does it increase the diagnostic yield of the biopsy but can also diagnose other associated conditions.